Hydrodynamic Optimization Method and Design Code for Stall-Regulated Hydrokinetic Turbine Rotors - Sale, D.; Jonkman, J.; Musial, W. (National Renewable Energy Laboratory (U.S.), 2009)
This report describes the adaptation of a wind turbine performance code for use in the development of a general use design code and optimization method for stall-regulated horizontal-axis hydrokinetic turbine rotors. This rotor optimization code couples a modern genetic algorithm and blade-element momentum performance code in a user-friendly graphical user interface (GUI) that allows for rapid and intuitive design of optimal stall-regulated rotors. This optimization method calculates the optimal chord, twist, and hydrofoil distributions which maximize the hydrodynamic efficiency and ensure that the rotor produces an ideal power curve and avoids cavitation. Optimizing a rotor for maximum efficiency does not necessarily create a turbine with the lowest cost of energy, but maximizing the efficiency is an excellent criterion to use as a first pass in the design process. To test the capabilities of this optimization method, two conceptual rotors were designed which successfully met the design objectives.